2017
DOI: 10.3847/1538-4357/aa71ae
|View full text |Cite
|
Sign up to set email alerts
|

A Complete ALMA Map of the Fomalhaut Debris Disk

Abstract: We present ALMA mosaic observations at 1.3mm (223 GHz) of the Fomalhaut system with a sensitivity of 14μJy/beam. These observations provide the first millimeter map of the continuum dust emission from the complete outer debris disk with uniform sensitivity, enabling the first conclusive detection of apocenter glow. We adopt an MCMC modeling approach that accounts for the eccentric orbital parameters of a collection of particles within the disk. The outer belt is radially confined with an inner edge of 136.3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
92
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 51 publications
(128 reference statements)
11
92
1
Order By: Relevance
“…Fomalhaut's disk (see Fig. 1) is perhaps a better example, being brighter and larger on the sky so that the offset and asymmetries are more clearly seen (Kalas et al 2005;MacGregor et al 2017), with additional azimuthal structure also evident (Kalas et al 2013).…”
Section: Dynamical Structuresmentioning
confidence: 99%
“…Fomalhaut's disk (see Fig. 1) is perhaps a better example, being brighter and larger on the sky so that the offset and asymmetries are more clearly seen (Kalas et al 2005;MacGregor et al 2017), with additional azimuthal structure also evident (Kalas et al 2013).…”
Section: Dynamical Structuresmentioning
confidence: 99%
“…Disk morphologies suggestive of influences from unseen planets, such as resonance clumps (Wyatt 2003) and/or apo-center glow (Pan et al 2016), are also best observed at submillimeter/millimeter wavelengths (e.g., Ertel et al 2012;Löhne et al 2017). Existing ALMA data on debris disks show a large variety of Kuiper-belt analogs: some systems have very narrow rings of parent bodies (e.g., Fomalhaut, Boley et al 2012;MacGregor et al 2017, andEri, Booth et al 2017), and some have either multiple rings (HD 107146, Ricci et al 2015a) or broad disks (HR 8799, Booth et al 2016;τ Ceti, MacGregor et al 2016;61 Vir, Marino et al 2017). The parent body distributions are therefore giving insights to the possible overall structure of the planetary systems.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the warm components is less certain, as they reside closer to the star and cannot easily be spatially resolved. For example, the nearby (7.7 pc) star Fomalhaut hosts a well-studied cold belt that has been resolved at several wavelengths (Kalas et al 2005;Acke et al 2012;Boley et al 2012;MacGregor et al 2017). From analyses of its SED and infrared images, Fomalhaut also hosts a warm component (Stapelfeldt et al 2004;Su et al 2013), but obtaining resolved images of this warm component to confirm its properties remains difficult .…”
Section: Introductionmentioning
confidence: 99%